Construction Analysis of Penal Mediation and Restorative Justice on Crime Settlement in the Indonesian Criminal Justice System - Andi ALif Kumullah DG. Pahare; Syamsuddin Muchtar; Muhammad Basri (IHSA Institute, 2023)
This research intends to analyze the existence of restorative justice and penal mediation in the Indonesian criminal justice system and to analyze the scope of the concept of restorative justice and penal mediation in the Indonesian criminal justice system. The research method used, normative juridical, is library law research which is carried out by examining library materials or secondary data sourced from primary, secondary, and tertiary legal materials. The research results obtained are the existence of restorative justice and penal mediation in the Indonesian Criminal Justice System. Number 11 of 2012 concerning the Juvenile Criminal Justice System. Restorative justice is a design of criminal justice that pays for the interests or needs of victims of victims, families and affected communities on the basis of the accountability of the perpetrators of criminal acts. So that it is necessary to strengthen the normative framework as a law enforcement effort from restorative justice to make law, both in a narrow formal sense and in a broad material sense, a guideline for behavior in every legal act, both by the legal subjects concerned and by law enforcement officials who are officially given the task and authority by law. Therefore, a rule that has legal certainty regarding restorative justice should be designed by a sovereign institution so that it has legal certainty. This is regulated in the 1945 Constitution of the Republic of Indonesia Article 20 paragraph (1) that